Perspektive učenja slovenskega jezika v Varaždinski županiji - Medvešek, Mojca (Jezik in slovstvo, 2017)
The organisation of Slovenian language learning as an extracurricular activity in the Varaždin County is an important achievement for the Slovenian community, as well as for the preservation of language vitality. By carrying out a survey amongst students attending Slovenian classes and their parents, we sought answers to the following questions: Who are the children attending classes of Slovenian language - are they Slovenian minority members or others? Is Slovenian the first or the second/foreign language for these students? What was the children's and parents' motivation for Slovenian language acquisition? What are their attitudes towards the use and significance of Slovenian and other languages? How satisfied are they with the language learning process? Based on an analysis of the responses of the students and parents, we try to assess the perspective of Slovenian language learning in the Varaždin County.
Keywords: Slovenci; Slovenes; jezikovne manjšine; Varaždinska županija (Hrvaška); slovenščina; Slovene; učenje in poučevanje jezikov; izobraževalni sistemi